Eu(III)-Functionalized MIL-124 as Fluorescent Probe for Highly Selectively Sensing Ions and Organic Small Molecules Especially for Fe(III) and Fe(II) - Xu, Xiao-Yu; Yan, Bing (ACS applied materials & interfaces, 2015)
A layerlike MOF (MIL-124, orGa2(OH)4(C9O6H4)) has been prepared and chosen as a parent compound to encapsulate Eu3+ cations by one uncoordinated carbonyl group in its pores. The Eu3+-incorporated sample (Eu3+@MIL-124) is fully characterized, which shows excellent luminescence and good fluorescence stability in water or other organic solvents. Subsequently, we choose Eu3+@MIL-124 as sensitive probe for sensing metal ions, anions, and organic small molecules because of its robust framework. Studying of the luminescence properties reveals that the complex Eu3+@MIL-124 was developed as a highly selective and sensitive probe for detection of Fe3+ (detection limit, 0.28 μM) and Fe2+ ions through fluorescence quenching of Eu3+ and MOF over other metal ions. In connection to this, a probable sensing mechanism was also discussed in this paper. In addition, when Eu3+@MIL-124 was immersed in the different anions solutions and organic solvents, it also shows highly selective for Cr2O7 2–(detection limit, 0.15 μM)and acetone. Remarkably, it is the first Eu-doped MOF to exhibit an excellent ability for the detection of Fe3+ and Fe2+ in an aqueous environment without any structural disintegration of the framework.